Efektivitas Penggunaan Media Audio Visual Terhadap Prestasi Belajar Siswa Kelas XI Pada Mata Pelajaran Akidah Akhlak Di MA Al-Ihsan Kalikejambon Tembelang Jombang - auliyah wahyuni; Emi Lilawati (JoEMS (Journal of Education and Management Studies), 2020)
Student learning achievements are strongly influenced by the various efforts undertaken by educators on the learning process, as in MA Al-Ihsan The use of audio visual media that has been properly applied by educators on subjects of moral faith, So that student learning achievements are more likely to increase. This study examines the effectiveness of the use of audio visual media on the learning achievement of XI class students on the subjects of the Islamic faith Al-Ihsan Kalikejambon. The problem that the researcher will solve is 1) how to use audio visual media in the subject of class XI in MA Al-Ihsan Kalikejambon. 2) How to study students ' achievements. 3) How the effectiveness of the use of audio visual media to the learning achievement of class XI students This research is a type of field research with a quantitative approach. Data collection methods (1) Observation for the use of audio visual media, (2) poll to determine the effectiveness of the use of audio visual media, (3) documentation for the achievement of students of XI MA al-Ihsan class, as well as the necessary data By researchers. The data analysis technique used is statistical analysis or statistical method, that is by using correlation test Product Moment. For that, researchers choose the research object of an educator in MA Al-Ihsan Kalikejambon and because researchers use the research population, then take all learners with a total of 74 Based on the results of the observation conducted by the researcher with the presentation of observation sheet 82.23. The result of data analysis was obtained average student achievement value of 82 with good category. In addition, in accordance with the calculation of the analysis of the correlation Product Moment test to determine the efficiency of the use of audio visual media on the learning achievement of the class XI students on the subject of morality in the MA Al-Ihsan Kalikejambon Tembelang Jombang with data calculation results r_ (count) = 0.514 > r_ (table) = 0.2287 with enough level categories, as well as showing that the value of Sig = 0.007 < 0.5 means that there is a effectiveness of the use of audio visual media to student learning achievements Class XI in the eyes of the teaching of the students Al-Ihsan Kalikejambon Tembelang Jombang with a relationship of 29.3%.